'They got a project mentality’: Theorizing neighborhood dis-identification and the paradox of belonging through the lens of ‘the Ghetto’. - Blokland, Talja (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
In a housing project in a small college town on the American East coast, a project that residents call ‘the Ghetto’, city administrators, social workers and politicians alike have often argued that housing projects offer living conditions that are not beneficial to the residents because, in a causal argument, they do not care about their community. Caring about the community is associated in public discourse and urban studies alike with positive identifications, and positive identifications with a sense of belonging, and sense of belonging with community. Based on long-term ethnographic research, this paper aims to critically discuss the question of how, on a meta-theoretical level, sense of belonging, community and positive identifications with a place are connected, showing that such connections are less obvious than sometimes suggested. Drawing on fieldwork on discourses of dis-identification and distancing in daily routines that constitute de-facto community as urban practice, this paper argues that first, sense of belonging and identification develops in an individual agents’ perspective, whereas community is relational and collective. This contrast explains the paradox of belonging: people say that others have ‘a project mentality’ and that they themselves do not ‘belong’ in the projects. Yet at the same time much of their networks and daily interactions consist of doing community locally. Second, this paper argues that usual explanations of simple stigma coping strategies - discursive constructions of dis-identification as a way of stigma - may play some role but do not suffice as a full explanation.